Eicosapentaenoic acid-enriched phospholipids improve atherosclerosis by mediating cholesterol metabolism. (May 2017) - Ding, Lin; Zhang, Lingyu; Wen, Min; Che, Hongxia; Du, Lei; Wang, Jingfeng; Xue, Changhu; Xu, Jie; Wang, Yuming
Highlights: Dietary EPA-PL was superior to DHA-PL on reducing atherosclerosis via distinct pathway. EPA-PL significantly reduced serum cholesterol level, while DHA-PL was ineffective. DHA-PL was superior to EPA-PL in suppressing arotic inflammatory. Abstract: Dietary fish oil could prevent and treat atherosclerosis by improving lipid metabolism; in apolipoprotein E-deficient (apoE −/− ) mice, it was ineffective at lowering serum lipid levels but still showed anti-atherosclerosis action. To date, no direct evidence has comparatively evaluated the effect of docosahexaenoic acid-enriched and eicosapentaenoic acid-enriched phospholipids (DHA-PL and EPA-PL) on atherosclerosis in apoE −/− mice. The present study suggested that both 1% dietary DHA-PL and EPA-PL could significantly reduce atherosclerotic lesions (37.4% and 53.4%, respectively) in high fat diet apoE −/− mice. EPA-PL significantly decreased serum and hepatic lipid levels, by mediating mRNA and protein levels of genes related to hepatic cholesterol metabolism, whereas DHA-PL was ineffective. In the suppression of aortic proinflammatory cytokines, DHA-PL was superior to EPA-PL at reducing TNF-α, IL-6, and IL-1β transcription. In conclusion, the action of DHA-PL was simply anti-inflammatory, and that of EPA-PL was mainly the improvement of lipid metabolism in the amelioration of atherosclerosis.